CALIFORNIA UPDATE - GREFE,EA (Tufts Archival Research Center, 2007)
Missing Attachments; Philip Morris USA memo from Edward Grefe offering an update on activities in California. Covers media activity, citing good results from TV and radio ads and plans for a new billboard ad and a new newspaper ad. Asserts that voter contact is good. Discusses the Speakers Bureau, direct mail, and point of sale materials. Warns that opposition may be mounting.